Editorial - Van Damme, Patrick (Afrika Focus, 2014)
The present issue of Afrika Focus delves into the way in which the Democratic (what’s in a word...) Republic of Congo has been dealing with its ‘way to peace’, via an article that looks at the issue through a discourse analysis perspective. In another article, the growing pains that often accompany the road to democracy in Africa are illustrated by the case of Togo. A third piece in this issue, a case study from Kenya, examines the gum Arabic value chain. The gum is an adhesive and food additive, often used in sweets and soft drinks, and thus an important commodity bought by big multinational companies. For centuries, it has been a source of income for a number of sub-Sahara African countries. Moreover, wars have been fought over the staple – as recently as last year, May 2013, at least 60 people were killed in ethnic (...) clashes in Sudan's arid Darfur region, over land producing gum Arabic. The deaths were the result of an ongoing dispute between two ethnic groups in South Darfur, over pasture and acacia trees, from which the gum is obtained. The Gemir group accused the Beni-Halba community of trying to take away land it had owned for more than 300 years. This shows that even a neutral (to sweet) subject such as gum Arabic can help to illustrate, and even explain, the root causes of political unrest in a number of countries. And this brings us to the last and fourth article that, even though it deals with poetry, reiterates the same political thematic as highlighted above, as it deals with ‘contemporary Nigerian poets [that] have had to contend with the social and political problems besetting Nigeria’s landscape by using satire as a suitable medium’. Perhaps the latter is amongst the most viable – and maybe only – coping strategies to allow people to survive Nigeria’s (and any ‘difficult’ country’s) distressing environment: if you can’t beat them, laugh at them...